Hematological predictive markers for recurrent or metastatic squamous cell carcinomas of the head and neck treated with nivolumab: A multicenter study of 88 patients. (22nd May 2020) - Matsuki, Takashi; Okamoto, Isaku; Fushimi, Chihiro; Sawabe, Michi; Kawakita, Daisuke; Sato, Hiroki; Tsukahara, Kiyoaki; Kondo, Takahito; Okada, Takuro; Tada, Yuichiro; Miura, Kouki; Omura, Go; et al.
Abstract: Background: There is increasing evidence that immunotherapy with nivolumab, an anti‐programmed death 1 monoclonal antibody, is effective in the treatment of recurrent or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). However, the predictive role of hematological inflammatory markers such as neutrophil‐to‐lymphocyte ratio (NLR) and the modified Glasgow prognostic score (mGPS) in patients with R/M SCCHN treated with nivolumab remains unclear. Methods: We conducted a multi‐institutional cohort study to evaluate the impact of pretreatment NLR and mGPS on overall survival (OS) and progression‐free survival (PFS) in patients with R/M SCCHN treated with nivolumab in Japan. From 2012 to 2013, 102 patients were eligible, of whom 88 were finally included in the analysis. mGPS was calculated as follows: mGPS of 0, C‐reactive protein (CRP) ≤1.0 mg/dL; 1, CRP > 1.0 mg/dL; and 2, CRP > 1.0 mg/dL and albumin < 3.5 mg/dL. Optimal cutoff point of dichotomized NLR was calculated using the area under the receiver operating characteristic curve (AUROC). Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were estimated by Cox proportional hazard models adjusted by potential confounders. Results: Higher NLR was significantly associated with worse survival (1‐year OS: 45.3% vs 16.3%, log‐rank P ‐value < .001, adjusted HR: 4.40 (95% CIs: 1.78‐10.88); one‐year PFS: 39.1% vs 9.0%, P ‐value = .001, adjusted HR: 3.37 (95% CI: 1.64‐6.92)). In addition, high mGPS (=2) was significantly associated with worse survival compared to low mGPS (=0) (1‐year OS: 37.4% vs 26.1%, P ‐value = .004, adjusted HR: 4.20 (95% CI:1.54‐11.49); 1‐year PFS: 41.5% vs 24.8%, P ‐value = .007, adjusted HR: 2.01 (95% CI: 0.87‐4.68)). These associations were consistent with subgroup analyses stratified by potential confounders. Conclusions: Pretreatment NLR and mGPS might be predictive markers of survival in patients with R/M SCCHN treated with nivolumab. Abstract : Immunotherapy with nivolumab is effective in the treatment of R/M SCCHN. However, reliable predictive markers have remained unclear. Higher pre‐treatment NLR and mGPS were significantly associated with worse survival, suggesting that these markers may be predictors of treatment with nivolumab.